A review of models of distributed dry friction. Issue 2 (2016) - Zobova, A.A.
Abstract: Models of distributed dry friction are analysed. In constructing the models, it is assumed that contact exists between the two bodies over a certain area, with Amonton–Coulomb dry friction in each infinitesimal region of this area. Static models (Contensou–Erismann friction and its modifications) and dynamic models (phenomenological models, a dynamically combined model, and a viscoelastic base model) are examined, and the application of these models in systems for calculating mechanical systems is considered.